Bevacizumab in the treatment of ovarian cancer - Ramez N Eskander (Dove Medical Press, 2011)
Ramez N Eskander1, Leslie M Randall21Division of Gynecologic Oncology, Department of Obstetrics and Gynecology, University of California Irvine Medical Center, Orange, CA, USA; 2Division of Gynecologic Oncology, Department of Obstetrics and Gynecology, University of California, Irvine, Orange, CA, USAAbstract: Despite advances in surgical cytoreduction and cytotoxic chemotherapy, ovarian cancer continues to be the leading cause of death in women with gynecologic malignancy. Our understanding of the treatment of ovarian cancer was revolutionized with the discovery of platinum- and taxane-based adjuvant chemotherapy regimens. Since that time however, overall survival has been stable. Given the above, an emphasis has been placed on exploring alternative therapeutics. Recent research efforts have improved our understanding of the molecular biology of ovarian cancer and novel targeted treatment strategies have emerged. The most studied of these agents has been the monoclonal anti-vascular endothelial growth factor antibody bevacizumab. The purpose of this review is to discuss management issues related to the treatment of ovarian cancer, with a focus on the utilization of bevacizumab, summarizing applicable clinical trials, its potential benefits, and reported adverse events.Keywords: bevacizumab, ovarian cancer, molecular targeted therapy, VEGF, angiogenesis